Officials-translators and correspondence agencies in Italian society under French rule (Il Risorgimento. Rivista di storia moderna e contemporanea, 2024)
Investigating the interaction between translation practices, administrative practices and the dissemination of governmental knowledge in Napoleonic Italy, several themes converge. This article explores the role of officials entrusted with administrative translations and how the private market responded to the need for translation services within Italian society under French control. In fact, numerous correspondence agencies were established, offering assistance with bureaucratic procedures and, most of all, translations. The service, quickly emerged as the primary focus of these agencies, driven by the legislative demands of the era, that required to produce and process documentation in French and Italian.
Keywords: officials-translators, judicial and administrative practices, sworn translations, French language; correspondence agencies, Italian identity.